Structures of S-(pyridin-2-yl) 4-nitrobenzothioate, S-(pyridin-2-yl) 4-methylbenzothioate and S-(pyridin-2-yl) 4-methoxybenzothioate: building blocks for low-symmetry multifunctional tetrapyrroles - Senge, Mathias (My University, 2023)
The crystal structures of three S-(pyridin-2-yl) benzothioesters with varying para-phenyl substituents are presented, namely, S-(pyridin-2-yl) 4-nitrobenzo-thioate (1, C12H8N2O3S), S-(pyridin-2-yl) 4-methylbenzothioate (2, C13H11NO2S) and S-(pyridin-2-yl) 4-methoxybenzothioate (3, C13H11NO2S). This class of compounds are used in the mono-acylation of pyrrolic species to yield multifunctional tetrapyrroles. The structures presented herein are the first of their compound class. The dominant interactions present in this series are π–π stacking and C—H. . .O interactions, and as the para-phenyl motif changes from electron withdrawing (NO2, 1) to electron donating (OCH3, 3), changes are observed in the interactions present in the crystal packing, from predominant π–π stacking in 1 to exclusively C—H. . .O/N interactions (Caryl—H. . .Ocarbonyl, C—H. . .Omethoxy and Caryl—H. . .Npyridine) in 3.
Keywords: three S-(pyridin-2-yl) benzothioesters; electron donating; electron withdrawing; Crystal structure; Benzothioate derivatives; Hydrogen bonding